Introduction. Spain, Italy, Latin America: Protagonists, Routes, and Transatlantic Dialogues (Anclajes, 2021)
The articles included in this dossier propose an analysis of transatlantic relations between Latin America, Italy and Spain, specifically in the 20th and 21st centuries. From a transdisciplinary approach, they examine both intertextual and personal links and, therefore, also analyze specific figures, institutions, and cultural mediation groups.
Keywords: Transatlantic relations; Hispanic American literature; intertextuality; cultural mediation